Metadata_photography and the construction of meaning : a thesis presented in partial fulfilment of the requirements for the degree Master of Fine Arts to Massey University, College of Creative Arts, School of Fine Arts, Wellington, New Zealand - Nishioka, Mizuho (Massey University, 2010)
Photographic technology is increasingly respondent to a desire for the production and consumption of information. The current age of photography not only possesses the ability to capture the image, but also to capture photographic metadata as supplemental information. Engaging in the premise that the photographic image exists as an incomplete medium to the transfer of information, this research identifies the acquisition of data as a means to resolve interpretation and quantify the photographic image. Inhabiting a complex territory within this structure, the photographic image manifests multiplicity and operates as source, production, and capture of information. This work challenges the perceptions of how to engage with the dialogues created between the photographic image, and the externally appended metadata.
Keywords: Metadata for photographic images; Artistic photography; Discourse; Archive; Supplementation; Data; Photographic metadata; Fields of Research::410000 The Arts::410200 Visual Arts and Crafts Studies::410203 Photography studies